2013
DOI: 10.1098/rsbl.2012.0932
|View full text |Cite
|
Sign up to set email alerts
|

Forest refugia in Western and Central Africa as ‘museums’ of Mesozoic biodiversity

Abstract: The refugial speciation model, or 'species pump', is widely accepted in the context of tropical biogeography and has been advocated as an explanation for present species distributions in tropical Western and Central Africa. In order to test this hypothesis, a phylogeny of the cryptic arachnid order Ricinulei, based on four nuclear and mitochondrial DNA markers, was inferred. This ancient clade of litter-dwelling arthropods, endemic to the primary forests of Western and Central Africa and the Neotropics, might … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 27 publications
(39 reference statements)
3
49
1
Order By: Relevance
“…By studying one of the oldest terrestrial groups, with strikingly limited dispersal abilities, we were able to demonstrate that no oceanic dispersal is required to explain the current distribution of the group, as in recent reports on terrestrial leaf-litter arthropods [8,9,45,52]. A key contribution of this study is to show that the early diversification of velvet worms actually pre-dates continental split (figure 3), a result that resonates with recent molecular phylogenetic studies showing that cladogenesis in the major lineages of Cupressaceae (a gymnosperm family) [10] and amphibians [54] also pre-dated the break-up of Pangaea.…”
Section: (B) Ancestral Provincialismmentioning
confidence: 80%
See 1 more Smart Citation
“…By studying one of the oldest terrestrial groups, with strikingly limited dispersal abilities, we were able to demonstrate that no oceanic dispersal is required to explain the current distribution of the group, as in recent reports on terrestrial leaf-litter arthropods [8,9,45,52]. A key contribution of this study is to show that the early diversification of velvet worms actually pre-dates continental split (figure 3), a result that resonates with recent molecular phylogenetic studies showing that cladogenesis in the major lineages of Cupressaceae (a gymnosperm family) [10] and amphibians [54] also pre-dated the break-up of Pangaea.…”
Section: (B) Ancestral Provincialismmentioning
confidence: 80%
“…With the rise of molecular phylogenetics and divergence time estimation, there are now a plethora of examples depicting speciation processes over contiguous land. Barriers could be geographical (such as rivers [56], marine incursions [45] or rifting [49]) or ecological (most notably involving contraction of habitat in relation to past climatic changes [57]). In such a context, several factors could have led to the formation of barriers over Pangaea.…”
Section: (B) Ancestral Provincialismmentioning
confidence: 99%
“…Only one tropical African and four tropical Asian species of Onychophora are known, compared with 68 Neotropical species (Sena Oliveira et al., ). Among the 72 extant species of Ricinulei, 61 occur in the Neotropics, compared with 11 in tropical Africa and none in tropical Asia (Murienne et al., ). The low diversity of tropical African Ricinulei has been attributed to a sharp decline in species richness resulting from the reduction and loss of forest refugia during past phases of severe aridification (Axelrod, ; Raven and Axelrod, ; Hamilton, ; Axelrod and Raven, ; Whitmore, ; Murienne et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…However, molecular dating estimates in several plant and animal clades have shown that many species originated before the start of the Pleistocene, suggesting that forest refugia patterns reflect mainly Pliocene climatic fluctuation (Plana et al , ; Voelker et al , ). This led to the idea that lowland rainforests are museums of diversity (Table , Murienne et al , ). In other studies, these lowland regions have been found to be concentrations of old and widespread lineages, especially in birds (Table ; Fjeldså, ; Fjeldså & Lovett, ; Fjeldså & Bowie, ; Fjeldså et al , ).…”
Section: Introductionmentioning
confidence: 99%